PERANCANGAN APLIKASI e-SCM PADA PT CAHAYA BUANA FURINDOTAMA - Honni Honni; Robertus Tang Herman; Erick Christanto (Bina Nusantara University, 2008)
PT Cahaya Buana Furindotama is a company incorporated in the Olympic Group. This company is a manufacturingcompany which produces furniture and household-wares made from plastic material. Problems en countered were rawmaterial shortage and production delay, though the company already had a partnership with several suppliers because ofthe un-integrated data and there was a “human error” in data entry. Results of the problem were the company could losemarket share and threatened with competitors’ position. Based on the problems which arose, it was proposed to use an e-SCMapplication system at the company because e-SCM application system could help the company to manage flow of raw materialbetter and strengthen the company’s relationship between suppliers and distributors. The methods used were Porter’s FiveForces to analyze the company’s position in market and SWOT Method to determine a strategy could be used by the company.Based on the internal matrix (IFE), the result obtained was 3:08. Whereas, the external matrix (EFE), the result obtained was3:34. Based on both results, it can be concluded that the company is in a strong position in matrix IE. Whereas, the strategyused is Strengths-Opportunity (SO) which is in SWOT matrix. It is expected that the SO strategy and e-SCM applicationsystem, the company can be more strength its position in the market.Keywords: e-SCM, SWOT, internal matrix, external matrix